The Development of Greenhouse Air Humidity Control System Using PWM (Pulse Width Modulation) - Goldramijaya, Wily; Sulastri, Ni Nyoman; Wijaya, I Made Anom S.; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Control systems are widely applied in agriculture, such as using microcontrollers to control humidity in greenhouses. Lack of accuracy in conditioning the humidity in indoor farming affects plant growth and productivity, especially in microgreens. The humidity of the planting media indirectly affects the air humidity through evaporation. Therefore, a system is required to control and monitor air and planting media humidity. The purpose of this study was to design and build an air humidity control system using PWM (Pulse Width Modulation) in a greenhouse equipped with a monitoring and automatic irrigation system. The system control employed Arduino UNO ATmega328P as a microcontroller connected to the DHT22 sensor as an air humidity sensor, a capacitive soil moisture sensor as a humidity sensor for the planting media, relay to control misting and irrigation pump. The microcontroller was also connected to a driver as a DC fan control with PWM control, four DC fan as airflow suppliers and dehumidifiers, and LCD 16x2 as a monitoring system. The system used the air humidity setting points for microgreens which were entered manually through coding. The result of this research was a lean-to greenhouse prototype with a DHT22 sensor with air humidity error values of DHT22(1) 3.09% and DHT22(2) 3.34%. The system successfully read and displayed data and provided output with a response time of irrigation and misting systems of 78mS and 145mS, using a delay of 2 seconds. The PWM control of the DC fan was able to reduce and maintain the air humidity within the optimum range for microgreen growth by increasing as well as decreasing the DC fans’ RPM, which was based on its duty cycle value